Onset of Neoglaciation in the Southern Hemisphere - Porter, Stephen C. (Journal of quaternary science, 2000)
A review of evidence documenting an early Neoglacial (mid‐Holocene) advance of mountain glaciers in South America and New Zealand reveals that of 16 glaciers for which radiocarbon age control exists, only two have associated dates that may approximate the culmination of an advance. Advances of the remaining glaciers are controlled only by minimum or maximum limiting ages. Additional dates for several New Zealand glaciers are based on weathering‐rind measurements having large potential errors. Twelve of the glaciers now terminate or have terminated in lakes or in tidewater and are subject to instabilities associated with calving termini. An extensive debris cover in the ablation zone of nearly half of the glaciers makes their moraine succession potentially suspect as a record of detailed climatic variation. The two glaciers with seemingly reliable age control are located in valleys where large rock avalanches could affect glacier mass balance and lead to random advances, or where rock avalanche deposits might easily be mistaken for moraines and tills. The early Neoglacial interval has been defined primarily based on this set of data. The ages, taken at face value, suggest that the early Neoglacial advance culminated between ca. 5400 and 4900 cal yr ago (ca. 4600–4400 14C yr BP). This chronology, however, should remain provisional until improved age control is obtained for a large population of glaciers based on closely bracketing radiocarbon dates and/or an adequate number of cosmogenic isotope ages. Data from calving glaciers and those subject to rock‐avalanche activity should be avoided or assessed critically. Copyright © 2000 John Wiley & Sons, Ltd.